Relationship between market power and income diversification of Vietnamese commercial banks - Ta, Huyen Thanh; Pham, Linh Hong; Do, Hang Thu; Nguyen, Huong Thi Diem (Asian Economic and Financial Review, 2025)
This study explores the intricate relationship between market power and income diversification in Vietnamese commercial banks during the period 2007–2021, addressing gaps in the existing literature on emerging markets. Using the Panel Vector Autoregression (PVAR) model, it looks at how these two variables affect each other and how they change over time, taking into account things like bank size, business efficiency, and credit risk. The findings highlight a complex interplay: banks with higher market power exhibit reduced motivation to diversify their income sources, supporting the Quiet Life Hypothesis. However, under certain conditions, income diversification is shown to enhance market power by leveraging expanded business activities. The study also reveals that scale negatively affects both market power and diversification, whereas higher profitability (ROA) promotes both dimensions. Furthermore, listed banks demonstrate greater market power compared to their non-listed counterparts, although no significant difference is observed in their diversification levels. These insights offer valuable implications for policymakers and practitioners, emphasizing the need for tailored diversification strategies that align with market conditions and competitive pressures. By integrating the PVAR methodology and focusing on the unique context of Vietnam’s banking sector, this research provides both theoretical contributions and practical recommendations to enhance the competitiveness and stability of commercial banks in emerging economies.